Unsecured debt, consumer bankruptcy, and small business - Césaire A. Meh; Yaz Terajima (Bank of Canada, 2008)
In this paper we develop a quantitative model of entrepreneurial activity (risk-taking) and consumer bankruptcy choices and use the model to study the effects of bankruptcy regulations on entrepreneurial activity, bankruptcy rate and welfare. We show that eliminating bankruptcy exemptions leads to a modest increase in the fraction of entrepreneurs, a large decrease in the overall bankruptcy rate and a significant welfare gain. In contrast, eliminating the whole consumer bankruptcy system leads to a large fall in the fraction of entrepreneurs and a substantial welfare loss. These two findings suggest that the consumer bankruptcy system is desirable but it must be well-designed with regard to bankruptcy asset exemptions. In particular, excessive bankruptcy exemptions can be counter-productive. Finally, we argue that entrepreneurial activity is important when studying different bankruptcy rules or regulations.
Keywords: D31; E21; J23; 330; Economic models; Financial stability; Financial system regulation and policies; Insolvenzrecht; Unternehmensplanung; Entscheidung bei Risiko; Investition; Konsumentenverhalten; Konkurs; Wohlfahrtseffekt; USA